2018
DOI: 10.1063/1.5022669
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of interaction-strength interpolation formulas for gold and silver clusters

Abstract: The performance of functionals based on the idea of interpolating between the weak- and the strong-interaction limits the global adiabatic-connection integrand is carefully studied for the challenging case of noble-metal clusters. Different interpolation formulas are considered and various features of this approach are analyzed. It is found that these functionals, when used as a correlation correction to Hartree-Fock, are quite robust for the description of atomization energies, while performing less well for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

6
4

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 131 publications
(170 reference statements)
1
43
0
Order By: Relevance
“…It has also been found that the Wilson-Levy functional 24 provides a decent generalized gradient approximation (GGA) of E HF c [ρ HF ] for ionization energies 25 and for non-covalent interaction energies. 26,27 More recently, it has been observed that rather accurate interaction energies, 28,29 again especially for non-covalent complexes, 30 can be obtained by modeling the HF correlation energy E HF c with an interpolation between the second-order Møller-Plesset perturbation theory (MP2) and a large coupling-strength limit, which is approximated with the strong-interaction DFT functionals [31][32][33] of the HF density. These interpolations can easily be corrected from their sizeconsistency error 30 and have been shown to also provide a diagnostic indicator for the accuracy of MP2 for non-covalent interactions.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that the Wilson-Levy functional 24 provides a decent generalized gradient approximation (GGA) of E HF c [ρ HF ] for ionization energies 25 and for non-covalent interaction energies. 26,27 More recently, it has been observed that rather accurate interaction energies, 28,29 again especially for non-covalent complexes, 30 can be obtained by modeling the HF correlation energy E HF c with an interpolation between the second-order Møller-Plesset perturbation theory (MP2) and a large coupling-strength limit, which is approximated with the strong-interaction DFT functionals [31][32][33] of the HF density. These interpolations can easily be corrected from their sizeconsistency error 30 and have been shown to also provide a diagnostic indicator for the accuracy of MP2 for non-covalent interactions.…”
Section: Introductionmentioning
confidence: 99%
“…This idea was proposed by Seidl and co-workers in the context of the DFT AC. 20,44 Recent papers have also explored its use in the context of the HF AC, obtaining rather good results for interaction energies, particularly 45,46 (but not only 47 ) of non-covalently bonded systems. To use this approach in the HF AC context, we employ the following SPL (after Seidl, Perdew and Levy) interpolation form 44…”
Section: Practical Predictor For the Accuracy Of The Mp2 Theory When ...mentioning
confidence: 99%
“…In Fig. 5 we show the potential in (50) for R = 15. Via (42), δF ZPE /δρ(x) indeed introduces a correction in the mid-bond region.…”
Section: Exchange-correlation Potential For a 1d Dimermentioning
confidence: 99%